The Principle of Erga Omnes and Legal Certainty in the Execution of Administrative Court Decisions - Maalikatussofa -; Muh. Ali Masnun; Fahri Hidayatullah (Indonesian Journal of Administrative Law and Local Government, 2026)
This study analyzes the binding force of Administrative Court decisions on administrative bodies that are not formally parties to the dispute, as well as the legal implications of non-compliance with these decisions on the certainty of the employment status of civil servants. The research method used is normative legal analysis with a regulatory, conceptual, and case-based approach. The results of the study show that PTUN decisions that have permanent legal force are res judicata and have erga omnes binding force, thereby creating a normative obligation for all administrative authorities to implement them, even if they were not directly involved in the litigation process. Ignoring these decisions creates legal uncertainty that is contrary to the principle of legal certainty in the General Principles of Good Governance. This finding emphasizes the importance of progressive interpretation of the binding force of administrative court decisions and encourages administrative authorities to comply with decisions that have permanent legal force and provide legal mechanisms for aggrieved parties to effectively demand legal certainty.